2012
DOI: 10.1111/j.1365-2125.2012.04200.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic variation in the P2RX7 gene on pharmacodynamics of a P2X7 receptor antagonist: a prospective genotyping approach

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Analysis of allelic variation in large populations has identified numerous single nucleotide polymorphisms (SNPs) in the P2RX7 gene. In vitro transfection has demonstrated SNP‐dependent alterations (gain or loss) of P2X7 receptor function, as measured by ATP‐induced ethidium uptake and interleukin‐1β production. WHAT THIS STUDY ADDS • We provide definitive evidence of SNP‐dependent alteration in P2X7 receptor pharmacodynamics to a specific antagonist (GSK1370319A) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…As mentioned above, a major challenge is to understand which polymorphic variations of the P2X7R have relevance to which disease and to fit patients with different polymorphisms to the P2X7R antagonist that would have the greatest efficacy for that variant. For example, the responses of human leukocytes to GSK1370319A were significantly altered, directly related to the SNP genotype, there being a 6.7-fold difference in the inhibition of ATP-stimulated IL-1β release by GSK1370319A between individuals with the homozygous gain- and loss-of-function genotypes [ 223 ]. A correlation was found between some gain-of-function and loss-of-function P2X7R SNPs, transfected into HEK-293 cells, and the expression of the channel protein.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, a major challenge is to understand which polymorphic variations of the P2X7R have relevance to which disease and to fit patients with different polymorphisms to the P2X7R antagonist that would have the greatest efficacy for that variant. For example, the responses of human leukocytes to GSK1370319A were significantly altered, directly related to the SNP genotype, there being a 6.7-fold difference in the inhibition of ATP-stimulated IL-1β release by GSK1370319A between individuals with the homozygous gain- and loss-of-function genotypes [ 223 ]. A correlation was found between some gain-of-function and loss-of-function P2X7R SNPs, transfected into HEK-293 cells, and the expression of the channel protein.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P2X7 variants, including SNPs and splice isoforms, are likely to play a role in the differential activity of these compounds both between and within species. For example, N-[(2,4-dichlorophenyl)methyl]-1-methyl-5-oxo-l-prolinamide (GSK1370319A) has an almost 7-fold higher IC 50 value for ATP-induced IL-1b in human blood cultures from individuals with the A348T gain-of-function SNP than those from individuals with the E496A loss-of-function SNP (McHugh et al, 2012). Thus, given that human P2X7 is highly polymorphic (see section VIII), this has ramifications for the future use of P2X7 antagonists in treating human disorders.…”
Section: Modulators Of P2x7 Receptor Activationmentioning
confidence: 99%
“…However, the possibility remains that the efficacy of these P2X7 antagonists is dependent on P2RX7 genotype, as indicated in other in vitro studies using GSK1370319A (McHugh et al, 2012). Thus, it may be essential to stratify clinical data by P2RX7 genotype to detect therapeutic benefits of P2X7 blockade.…”
mentioning
confidence: 99%
“…We now know that minor genetic variations in the drug target may also lead to inter-individual variation in drug responses. A recent study showed that an exploratory new drug differed by 10 fold in affinity for its target, the P2X7 ion-channel, solely depending on two polymorphisms in the protein 19 , and a single polymorphism in the TNF-alpha 1 receptor can predict an adverse effect of TNF antagonist treatment 20 . Polymorphisms may be unrelated to known disease but determine which patients do and do not respond to a drug.…”
Section: Why Do We Need Large Collections Of Hipscs?mentioning
confidence: 99%